Teacher Education Students’ Preferred Learning Styles in the New Normal: Basis for Enhancing Pedagogies - Quejado, Ma. Rosario M.; Recede, Reynald Alfred A.; Carnecer, Rosario B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
The students’ preferred learning style is a very important part of the teaching and learning process. In selecting the most appropriate pedagogy to teach a lesson, the diversity of learners must be taken into serious consideration. The study examined the preferred learning styles of teacher educations students in Pamantasan ng Lungsod ng Marikina, Philippines during the time of the Covid 19 pandemic. A survey was conducted among 282 college students taking education course. Descriptive research design was used to analyze the data gathered during the investigation. Results showed that both male (WM=3.06) and female (WM=3.11) teacher education students scored highest on the visual learning style meaning they learn best when shown instructional materials in the form of pictures and videos. However, it was also revealed that female students learn better in terms of visual style as compared to their male counterpart. Hence, it is recommended that college instructors and professors consider and take a look at the teacher education students’ preferred learning styles when crafting teaching strategies for their students even in remote learning in the time of pandemic.